2016
DOI: 10.1083/jcb.201509023
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin 1 regulates spines and synaptic plasticity via LIMK1/cofilin-mediated actin reorganization

Abstract: The C-terminal domain of NLG1 is sufficient to enhance spine and synapse number and to modulate synaptic plasticity, and it exerts these effects via its interaction with SPAR and the subsequent activation of LIMK1/cofilin-mediated actin reorganization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 65 publications
5
67
0
Order By: Relevance
“…It reduces the activation of depolymerization of ADF/cofilin. This subsequently interferes with actin depolymerization, promotes actin cytoskeletal remodeling and cell pseudopodia formation, and induces EMT, thereby promoting tumor invasion and metastasis3649. The present study further confirmed that the expression and phosphorylation levels of LIMK1 significantly increased during colon cancer cell invasion and migration.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It reduces the activation of depolymerization of ADF/cofilin. This subsequently interferes with actin depolymerization, promotes actin cytoskeletal remodeling and cell pseudopodia formation, and induces EMT, thereby promoting tumor invasion and metastasis3649. The present study further confirmed that the expression and phosphorylation levels of LIMK1 significantly increased during colon cancer cell invasion and migration.…”
Section: Discussionsupporting
confidence: 81%
“…Destrin is also expressed in all colon cancer cell lines examined, and involved in the colon cancer cell migration and invasion35. LIMK1 is involved in the migration and invasion of tumor cells in a number of ways, such as regulating the ADF/cofilin activity to affect actin cytoskeleton remodeling36, thereby promoting tumor cell migration and invasion373839. In agreement with these reports, it was found that LIMK1 and its downstream molecule destrin (ADF) were highly expressed in colon cancer tissues.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, a number of membrane lipids, especially phosphoinositides, are regulated by synaptic activities [71], which are known to play an important role in the regulation of actin polymerization near the plasma membrane [72]. Moreover, a recent study shows a novel activity-dependent mechanism of spine remodeling in which activity-dependent proteolytic cleavage of Neuroligin 1 generated a cytoplasmic C-terminal domain to activate LIM kinase 1, which inhibits ADF/cofilin leading to an increase in spine number and enhanced synaptic plasticity [73]. Finally, a number of actin-binding proteins have been shown to undergo activity-dependent translocation into dendritic spines during LTP, with specific sub-spine patterns and timing associated with distinct phases of spine remodeling [74].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that cofilin-dependent actin changes are required for spine regulation and hippocampal plasticity, in particular LTD (Meng et al, 2002;Jia et al, 2009;Rust et al, 2010;Huang et al, 2011;Eales et al, 2014;Todorovski et al, 2015;Liu et al, 2016), but whether its involvement in these processes is developmentally regulated remains unknown. This is an important question because LTD is strongly affected by the developmental stages of the brain (Kemp et al, 1999;Fitzjohn et al, 2001).…”
Section: Both Protein Level and Activity Of Cofilin Is Developmentallmentioning
confidence: 99%